Pengembangan Nilai Agama dan Moral Pada Masa Pandemi di TK Al-Hidayah Lumajang - Alawiyah, Fakhriyatus Shofa; Masruroh, Laila (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2020)
Abstract Forming a religious experience in early childhood means embedding religious roots in them. The religious experience that is implanted early, will be able to improve the character, personality and moral of the child. One of the efforts to develop religious and moral values of early childhood in the physical distancing is through the collaboration of teachers and parents. This study used a qualitative descriptive approach in TK Al-Hidayah Purworejo, Lumajang. Data collected by interview techniques and document studies using WhatsApp (phone, chat, voice note) and polls using Google forms. The data was analyzed by the analysis of the Miles and Huberman models and the validity test of data using the triangulation of the source and method, discussion with peers, using references. The results of this research that religious and moral values developed in children or students of TK al-Hidayah include: Know the religion that is embraced, work on worship, behave honestly, helper, responsibilities, maintain self-hygiene and the environment. To develop these values, the form of collaboration that teachers and parents use is a partnership or shared responsibilities model that emphasizes the coordination and cooperation of schools and families to develop communication and collaboration. Some forms of collaborative activities include building a relationship and communication with two-way applications based on WhatsApp Group (WAG), teachers provide daily assignments for children during the study at home, teachers give instructions for learning based television Republic of Indonesia (TVRI), learning the sheet based Activities Ramadan. Parents strive to accompany each and every activity and report the children's learning outcomes to the teachers.